NOVEL METHOD OF USING CHILLED AIR MACHINING ON UNIDIRECTIONAL CARBON FIBER REINFORCED PLASTIC FOR LONG TERM USAGE OF SOLID CARBIDE CUTTING TOOL - Muhamad Khairussaleh, Nor Khairusshima (2017)
Carbon fiber reinforced plastic (CFRP) is an expensive composite which has become valuable material as the demand for this composite increased in the industries. It is suitable to be used in automotive, aerospace and aircraft because of its properties which is stronger than steel and also stiffer than titanium while retaining its lighter weight. Fabrication of CFRP is through molding process but machining processes such as milling is needed especially during the component assembling stage. Even though, the development of fiber-reinforced plastic composites has led to advantages over metal, however, there are still some issues concerning the machinist. These include excessive tool wear and poor surface quality due to delamination and fiber pull-out during machining. Because there are at least two phases of materials in FRP, each with unique mechanical properties, the material removal mechanism is different from that observed when machining homogeneous materials, such as metals. To overcome these problems, polycrystalline diamond (PCD) is commonly used to machine FRP. However, it is costly as it takes longer to produce smoother surfaces compared to other cutting tools. Therefore, carbide cutting tools which are one of the hardest materials and cheaper compared to PCD, have been considered and often used in industry to machine CFRP. Although carbide cutting tools have the potential but its machining performance not as good as PCD’s. Chilled air is a near dry method which is not only environmentally friendly as it produces no chemical pollution, but it can also decrease tool wear and improve the surface quality. In this study, for chilled air machining, the cooled air will be applied to the cutting tool by using vortex tube. By hypothesis, by cooling down the heat generated during machining which is the main cause of tool wear and surface quality to occur, the production cost of CFRP can be reduced as well compared to dry machining.